“Christians and Mudejars: Perception and Power in Medieval Portuguese Society” - Barros, Maria Filomena Lopes de (2012)
The perception of otherness implies a new terminology that reduces the Muslim to the Moor in the parameters and contexts controlled by Christian powers. The assumption of this semantics by the group itself reveals a common cultural background based on a Portuguese linguistic community. Nevertheless, as a frontier group another terminology emerges from the dār al-Islām, the Ġarīb, in a re-interpretation from the external Muslim world that bounds the Christian Moor to the Muslim-Arabic culture and religion. The landmarks of a new Muslim identity in the Portuguese Kingdom shapes the group’s ethnocentrism in a double ascription to one culture, one king and one territory, as Moor, and to a transnational religious dimension, as Ġarīb.